Effect of fluoride-releasing fissure sealants on enamel demineralization. Issue 1 (April 2017) - Nakamura, Koichi; Abe, Shigeaki; Minamikawa, Hajime; Yawaka, Yasutaka
Abstract: Objective: The purpose of this study was to investigate the effect of three types of fissure sealant (resin-based fissure sealant, resin-based fissure sealant containing S-PRG filler, and resin-modified glass ionomer cement (RMGIC)-based fissure sealant) on the surrounding enamel. Materials and methods: Human deciduous molars were filled with fissure sealants and cut into 200 μm sections. Using an automatic pH-cycling system, the specimens were repeatedly demineralized and remineralized for 5 weeks. After automatic pH-cycling, integrated mineral loss (ΔIML) of the enamel around the fissure sealant was calculated. Twelve blocks of each fissure sealant were exposed to 10 mL of distilled deionized water at pH 6.3. Fluoride ion release, strontium ion release, and pH changes of the water were measured every week for 5 weeks. Results: The BeautiSealant and FujiIIILC sealant groups had a significantly lower mean ΔIML at 5 weeks than the control group. The rate of fluoride and strontium ion release was significantly greater for the FujiIIILC sealant group than that for the Teethmate F-1 2.0 and BeautiSealant groups. Conclusion: Fissure sealants that released a lot of fluoride and strontium ions showed decreased enamel demineralization.